The role of endoscopic ultrasonography in choledocholithiasis - Ülkü SARITAŞ,; Bülent YILDIRIM,; Uğur YILMAZ,; Burhan ŞAHİN,; Gülay TEMUÇİN,; Gönül GÜRKAYNAK, (Turkish Journal of Gastroenterology, 2020)
-